Structural and Magneto-mechanical Properties of Fe-Ni-Ga Alloys. (2016) - Jen, S.U.; Chiang, F.L.; Cheng, W.C.; Lo, Y.Y.; Pai, L.W.
Abstract: Fe81-X NiX Ga19 alloys, with x = 0 - 26 at.%Ni, were made from in induction furnace. The structural properties of each alloy were analyzed by x-ray and selected area diffraction within a plane-view transmission electron microscope image. For the Fe81 Ni19 alloy, it contains the disordered A2 (matrix) and ordered D03 phases, but when Fe has been replaced by Ni in the Fe81 Ga19 alloy, it contains the disordered A2 (matrix), ordered B2, and ordered D03 phases. From this study, it is concluded that the Fe70 Ni11 Ga19 alloy should be a good functional material for transducer and energy harvesting applications.